2019
DOI: 10.1021/acs.analchem.8b05801
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Dependence of Structurally Specific Isotopic Shifts in High-Field Ion Mobility Spectra

Abstract: Nearly all molecules incorporate at least one element with stable isotopes, yielding ubiquitous isotopologic envelopes in mass spectra. Those envelopes split in differential or field asymmetric waveform ion mobility (FAIMS) spectra depending on the ion geometry, enabling a new general approach to isomer delineation as we demonstrated for chloroanilines. Here, we report that analogous bromoanilines exhibit qualitatively distinct isotopic shifts under identical conditions, some changing signs depending on the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(111 citation statements)
references
References 50 publications
9
102
0
Order By: Relevance
“…The separations of isotopologues at different m/z and isotopomers at equal m/z are a priori orthogonal, rendering ΔE C and w R complementary descriptors. 31 Here, the w R metric confirms the differentiation of unresolved 2,4 and 2,5 from each other and {2,6; 3,4; 3,5}. The w R values at m/z = 256 follow those for single 13 C peaks, with wider margins ensuing from lower signal (Figure 7a).…”
Section: Journal Of the American Society For Mass Spectrometrysupporting
confidence: 65%
See 2 more Smart Citations
“…The separations of isotopologues at different m/z and isotopomers at equal m/z are a priori orthogonal, rendering ΔE C and w R complementary descriptors. 31 Here, the w R metric confirms the differentiation of unresolved 2,4 and 2,5 from each other and {2,6; 3,4; 3,5}. The w R values at m/z = 256 follow those for single 13 C peaks, with wider margins ensuing from lower signal (Figure 7a).…”
Section: Journal Of the American Society For Mass Spectrometrysupporting
confidence: 65%
“…As with E C shifts, one can multiplex the w R values to reduce the uncertainty. 31 In fact, the benchmarks (derived from average w R for m/z of 252 and 254 relative to m/z = 250) are now in the narrower 1.00−1.03 range with smaller margins of 0.01 (Figure 7a). These define w R ∼ 1.04 as the threshold of significance for broadening of other peaks.…”
Section: Journal Of the American Society For Mass Spectrometrymentioning
confidence: 95%
See 1 more Smart Citation
“…We note that resolution of some isotopomers has been achieved using FAIMS, , where separations take place based on the mobility of ions in both high and low electric fields. , However, the basis for these separations has not been established due to the fact that the FAIMS separation occurs in conjunction with significant ion heating (and likely induced structural changes) as well as other possible contributions such as partial ion dipole alignment due to the high fields involved. , …”
Section: Results and Discussionmentioning
confidence: 99%
“… However, the reported R p would be insufficient for much larger ions, and even greater challenges would arise with the use of lighter drift gases (e.g., helium) due to the smaller reduced mass differences. The only other isotopologue or isotopomer ion separations of which we are aware have used Field Asymmetric Ion Mobility Spectrometry (FAIMS), where R p values up to ∼500 have been demonstrated based upon differences in mobilities at very high vs low electric fields in mixtures of gases. , While these studies suggest that observed shifts for individual substitutions may be relatable to the ion’s structure, FAIMS incurs some significant, but not well characterized, extent of ion heating and potential structural perturbations due to the high fields used, as well as other possible contributions such as partial ion alignment in the field, making an understanding of the effects due to isotopic substitutions elusive. , …”
mentioning
confidence: 99%